Institutional reaction or dictatorial push? Tensions between Congress and the Executive at the beginning of the twentieth century (Estudios Sociales, 2019)
José Figueroa Alcorta’s decision to close the Congress sessions exposed the fragility of political alignments and the difficulties that the government had in building a stable parliamentary coalition. To explore the role that Congress played in the Argentine political system this article analyses the debates about the legitimacy of the so-called «coup d’état». It examines the disruptive nature of Figueroa Alcorta’s decision and attempts to contribute to the understanding of the relationships between the National Executive and Congress during the «Conservative Order» by comparing the 1908 crisis with political crises in the 1890s. Particular attention is paid to the power of the Executive, the legitimacy of representatives and the nature of the division of powers.
Keywords: parliament; coup; newspapers; executive power; political history